2018
DOI: 10.1016/j.apenergy.2017.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based validation of climatic zoning for building energy efficiency applications

Abstract: 10Climatic zoning for building energy efficiency applications is an important element in building energy policy and 11 regulations. There are several methodologies available to conduct climatic zoning, providing significantly different results. 12Currently, there are no procedures to assess the validity of a proposed climatic zoning, hindering the decision to use one 13 particular climatic zoning methodology instead of another. This paper introduces a quality index and a procedure to support 14 the validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Multivariable statistical analysis based on clustering methods makes it possible to obtain an efficient climate classification [27] and seem more coherent for building concerns [8]. Other studies confirmed the interest of clustering [28,29] and specifically of k-means clustering with Euclidean distance correlation as a measure of similarity for the classification of a climate in general [16,18] or adapted to a building [1,2,22,[30][31][32][33]. The quality and availability of the parameters used for climate classification are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariable statistical analysis based on clustering methods makes it possible to obtain an efficient climate classification [27] and seem more coherent for building concerns [8]. Other studies confirmed the interest of clustering [28,29] and specifically of k-means clustering with Euclidean distance correlation as a measure of similarity for the classification of a climate in general [16,18] or adapted to a building [1,2,22,[30][31][32][33]. The quality and availability of the parameters used for climate classification are essential.…”
Section: Introductionmentioning
confidence: 99%
“…These regulations are key instruments used to enforce minimum performance targets, to define subsidies and to implement strategies to achieve ambitious goals for energy conservation and CO2 emission reductions. Despite the relevance, most of the current climatic zonings methodologies are based on simplified weather parameters and are usually assumed to be correct and valid per se, being directly applied to building energy regulations without going through a validation process (Walsh et al, 2018a). These assumptions can lead to inconsistencies between the climatic zones and energy performance of individual buildings, consequently affecting the performance of the whole building stock and the effectiveness of building energy policies (Burleyson et al, 2017;M.…”
Section: Introductionmentioning
confidence: 99%
“…In that regard, a method to address climatic zoning validation using quantitative procedures has been recently reported in the literature (Walsh et al, 2018a). This method is based on building performance, rather than on weather data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations